Chemical composition and antioxidant activity of the fruit essential oil of Xanthium strumarium L. cultivated in Hai Duong province, Vietnam - Dang-Minh-Chanh Nguyen; Thi-Hoan Luong (Vietnam Journal of Science, Technology and Engineering, 2025)
Xanthium strumarium L., a species in the Asteraceae family, is well known for its use in traditional medicine. This study aimed to identify the chemical composition and evaluate the antioxidant activity of the essential oil (EO) extracted from the fruits of X. strumarium collected in Hai Duong province, Vietnam. The EO was obtained via steam distillation and analysed using gas chromatography-mass spectrometry (GC-MS). The results revealed 15 major compounds accounting for 93.88% of the total oil content. The dominant constituents included m-tolualdehyde (12.11%), 1,2-benzenedimethanol (11.87%), p-tolualdehyde (9.94%), caryophyllene oxide (9.28%), and endo-borneol (8.91%). The major chemical groups were oxygenated sesquiterpenes (26.79%) and aromatic compounds (39.72%). The antioxidant activity of the EO was assessed using three methods: ferricyanide reducing power, 2,2-diphenyl-1-picrylhydrazyl (DPPH), and 2,2'- Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging assays. The EO demonstrated strong radical scavenging activity, comparable to ascorbic acid, with IC50 values of 22.8 µg/ml (DPPH) and 22.1 µg/ml (ABTS). These findings indicate that the fruit EO of X. strumarium possesses a rich chemical profile and significant antioxidant potential, suggesting promising applications in pharmaceuticals and functional foods.